2005
DOI: 10.1103/physrevlett.94.112501
|View full text |Cite
|
Sign up to set email alerts
|

Half-Life of the Doubly Magicr-Process NucleusN78i

Abstract: Nuclei with magic numbers serve as important benchmarks in nuclear theory. In addition, neutronrich nuclei play an important role in the astrophysical rapid neutron-capture process (r-process). 78 Ni is the only doubly-magic nucleus that is also an important waiting point in the r-process, and serves as a major bottleneck in the synthesis of heavier elements. The half-life of 78 Ni has been experimentally deduced for the first time at the Coupled Cyclotron Facility of the National Superconducting Cyclotron La… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

6
4

Authors

Journals

citations
Cited by 163 publications
(97 citation statements)
references
References 29 publications
2
94
1
Order By: Relevance
“…The Maximum Likelihood analysis (MLH) is well suited for determining decay half-lives in cases with low statistics [37,71,72,73,74,75,76]. The method, described in appendix A, defines decay sequences for up to three generations following an implantation.…”
Section: β-Decay Half-lives From Maximum Likelihood Methodsmentioning
confidence: 99%
“…The Maximum Likelihood analysis (MLH) is well suited for determining decay half-lives in cases with low statistics [37,71,72,73,74,75,76]. The method, described in appendix A, defines decay sequences for up to three generations following an implantation.…”
Section: β-Decay Half-lives From Maximum Likelihood Methodsmentioning
confidence: 99%
“…For the nuclear species analyzed in Refs. [5,6,35,36,37], β-neutron coincidences associated with descendant nuclei other than the β-decay daughter were negligible. In this case, using the Batemann equations [38], it is possible to write explicitly the value of N ββn as:…”
Section: Measurement Of P Nmentioning
confidence: 99%
“…The speed of the r-process reaction sequence and the resulting abundances of the elements are significantly influenced by the β-decay properties of the nuclei involved, which are in turn directly related to the evolution of nuclear structure and deformation. In a recent measurement of the half life of the doubly-magic nucleus 78 Ni [8,9], it was shown that the persistence of the closed neutron and proton shells had a significant impact on the r-process abundance patterns, and theoretical predictions for the half life were significantly longer than observed.…”
Section: Introductionmentioning
confidence: 99%